Cover Image. (26th April 2022) - Yu, Xinliang
Abstract : The cover image is based on the Research Article Prediction of enantioselectivity in thiol addition to imines catalyzed by chiral phosphoric acids by Xinliang Yu, https://doi.org/10.1002/poc.4338 .